Discussion of the Research Results of Judo Games at the Initial Stage of Long-Term Training - Larisa Masenko (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
The article deals with the effects of improved methods of training 7–12 year old children at the initial stage of long-term training using specialized Judo Games. Modern methods of training in many sports, Judo in particular, are characterized by early specialization. In this regard there could be observed immaturity of some existing training programs when age-related features of beginners are not taken into consideration, and as a result children’s health is suffering unfortunate consequences. Methods of initial Judo training open vast space for perfection and development of this kind of sports. The author initiated and practiced teaching and training process at the IT (initial training) stage Judo beginners by using Judo games as means of full development of physical features and shaping combat skills. This experiment proved to be actual and practically valuable.